GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 621510612 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false. The dataset includes 621510612 records from 12708 constituent datasets: Please see http://www.gbif.org/occurrence/download/0040194-160910150852091 for full list of all constituents.
Keywords: GBIF; biodiversity; species occurrences